ANALISIS PERHITUNGAN POWER LINK BUDGET SISTEM KOMUNIKASI SERAT OPTIK PADA KOMPLEKS PERUMAHAN PRIMA HARAPAN REGENCY BEKASI MENGGUNAKAN GUI MATLAB - Muhammad Cahyo Kusumo (2023)
The development of telecommunications technology in optical fiber communication systems by sending light as an information wave. The increase in bandwidth and high data transfer speeds has driven the development of fiber optic-based networks to FTTH (Fiber to the Home) residential services, one of those are power link budget calculation processes. FTTH (Fiber to the Home) is a customer optical fiber communication network that can be accessed directly at home where Indihome by PT. Telkom is currently the largest provider in the market. In this final project, a power link budget calculation has been made to determine the performance of an optical fiber communication system using several methods. From the analysis of the tools used, output power and input power affect different calculation results. The calculation results using GUI Matlab produce an ONT power value of -22.24299 dBm indicating that the output results are not disturbed. The standardization value of the FTTH system is applied to one of Indihome's customer.